A Survey on Quantum Image Processing. Issue 4 (1st July 2018) - Cai, Yongquan; Lu, Xiaowei; Jiang, Nan
Abstract : Quantum image processing is the intersection of quantum computation and image processing. Due to it is a newly emerging thing, researchers are facing not only great opportunities but also many challenges to develop more efficient and practicable services. We provide a comprehensive survey on quantum image processing to gather the current mainstream and discuss the advances made in the area, including quantum image representations, processing algorithms, and image measurement. Moreover, some open challenges and future directions are pointed out to attract continued research efforts